COMPOSITIONAL AND TECHNOLOGICAL FOUNDATIONS FOR UTILIZING NATIONAL MINIATURE ELEMENTS IN MODERN GARMENT DECORATION - Mokhinur Rakhimdjonova; Malika Usmanova; Mokhinur Berdimurodova; Risolat Kuchkarova; Saodat Pardayeva (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the compositional and technological foundations of incorporating national miniature elements into the decoration of modern garments. The relevance of this research lies in the significant decline of interest in handcrafted miniature art due to the rapid advancement of contemporary technologies. Consequently, preserving national heritage and harmonizing it with modern design has become a crucial task. The paper analyzes the artistic-compositional principles of integrating miniature elements into clothing design, alongside the technical aspects of their application. Furthermore, the study examines the development of garment samples tailored for the image of the modern business woman based on these elements. The findings of this research contribute to the creation of innovative design solutions by blending traditional national artistic traditions with contemporary fashion.